Innovation in creative economy micro-enterprises : a multiple case study - Galuk, Mariana Bianchini (2016)
Purpose: Research about how creative economy grew considerably in last years, mainly by the increase of representation that this sector has in the global economy. It is believed that creative economy’s organizations have some characteristics that differentiate them for the traditional areas where creativity is relevant in the innovation process. Thus, this paper aims to analyse the process of innovation in the creative economy organizations. Originality/gap/relevance/implications: Due to still early literature in the Brazilian context, we expect to contribute to it in the business studies field. Key methodological aspects: We conducted an exploratory qualitative research study on four micro enterprises that are part of the creative industries. The theoretical approach was about innovation in creative organizations, so as it was possible to realize an analysis of innovation in the investigated business from three categories identified in the literature: organization, technology options and customers. Summary of key results: It was found that these organizations have some characteristics that differ from traditional sectors of the economy, both in the type of innovation and in the way the innovation process is managed. However, it is questionable whether the flexibility that both aids in the flow of ideas and information would be a reality in larger companies. Key considerations/conclusions: As contributions, this article raised a reflection on creativity and innovation in this segment and also on innovation in creative microenterprises.